Characterization of muscovado sugar - Balagat, Cherry Grace Rubio; Francisco, Maria Leonora dL (College of Home Economics, University of the Philippines Dilman, 2015)
The physicochemical and sensory properties of muscovado were characterized in this study in order to determine its suitability as a sucrose alternative. Six muscovado brands were found to have water activity values ranging from 0.529 to 0.630, pH of 4.66 to 5.63, % titratable acidity of 0.012 to 0.077%, total soluble solids of 10.64 to 11.14 Bx and invert sugar content of 29.7% to 30.7%. Powdered muscovado had L, a and b values of 31.32 to 51.06, 11.40 to 13.02 and 23.59 to 33.02, respectively, while 10% muscovado solutions had L, a and b values of 7.93 to 33.04, 20.03 to 24.92, 11.75 to 51.13,respectively, and ICUMSA color units of 5040 to 13578. Significant differences among the brands and noncompliance to standards were observed due to the lack of a standard processing method. Muscovado had a significantly higher aw, % TA, TSS and invert sugar content and a more acidic pH and a darker color than white sugar explained by the absence of refining during processing. In the 2-AFC evaluation, there was no significant difference in sweetness between (a) freshly-prepared muscovado and white sugar solutions; (b) freshly-prepared and overnight-refrigerated white sugar solutions; (c)overnight-refrigerated muscovado and white sugar solutions except for one pair of freshly-prepared and overnight-refrigerated muscovado solution. In the consumer acceptance test, black tea with muscovado obtained significantly higher intensity ratings in terms of brown color, black tea odor and sweetness but not in black tea flavor as compared to black tea with white sugar. There were also significant differences in the mean acceptance ratings of color and flavor but not in aroma, sweetness and overall acceptability. Muscovado can be a sucrose alternative but its different physicochemical and sensory properties must first be considered before using it in a food product.